The Role of Insulin-like Growth Factor-Binding Protein-3 in Cancer and Inflammation: From Molecular Mechanisms to Clinical Applications - hourolein arab; Mohammad Shokrzadeh; Mahboubeh Rahmati; Mohammad Reza Mofid (Journal of Mazandaran University of Medical Sciences)
Insulin-like growth factor binding protein-3 (IGFBP-3), a member of the IGFBP family, plays an extensive role in cellular growth regulation. By specifically binding to insulin-like growth factors (IGFs), this protein modulates their accessibility to specific receptors, thereby inhibiting IGFs and suppressing the growth of cancer cells. IGFBP-3 also exhibits IGF-independent functions, including the regulation of apoptosis, cell cycle control, autophagy, gene expression, and the inhibition of nuclear factor kappa-B (NF-κB). Given that chronic inflammation is recognized as a driver of cancer progression, the role of IGFBP-3 in suppressing the transcription factor NF-κB and its anti-inflammatory effects are particularly significant within tumor-promoting inflammatory conditions. However, in certain pathological contexts, this protein may contribute to cancer cell survival, highlighting its dual role in regulating cell death and survival. The dichotomous nature of IGFBP-3 has established it as an important target in cancer research, particularly in the context of inflammation and inflammation-associated malignancies. This narrative review explores both IGF-dependent and IGF-independent mechanisms of IGFBP-3, focusing on its role in cancer and inflammatory diseases. The study examines the association between alterations in IGFBP-3 expression and function with various malignancies and inflammatory conditions. Furthermore, it evaluates the therapeutic potential of IGFBP-3 in the treatment of oncology and inflammatory diseases. A deeper understanding of IGFBP-3's dual functionality and associated signaling pathways could facilitate the development of targeted therapeutic strategies against cancer and inflammation. This review presents novel perspectives on the clinical applications of IGFBP-3, including its potential as a standalone therapeutic agent, a pharmacological target in combination with standard treatment regimens (e.g., chemotherapy, radiotherapy, or immunotherapy), or as a molecular scaffold for novel drug design